Integrasi Kurikulum Pesantren dan Kurikulum Nasional: Analisis Manajemen terhadap Kualitas Lulusan Santri di Pondok Pesantren Ar-Rahman Malang - Wahyudi Widodo (Lembaga Yasin AlSys, 2026)
The integration of the pesantren curriculum and the national curriculum is an important strategy for Islamic educational institutions in producing graduates with strong academic, religious, and character competencies. However, the success of this integration is strongly determined by the effectiveness of educational management implemented by the institution. This study aims to analyze the management of the integration of the pesantren curriculum and the national curriculum and its contribution to the quality of santri graduates at Pondok Pesantren Ar-Rahman Malang. This study used a qualitative approach with a case study design. Data were obtained through observation, in-depth interviews, and documentation with informants consisting of the pesantren leader, deputy head for curriculum, teachers, ustaz, and santri. The data were analyzed using the Miles, Huberman, and Saldaña interactive model through the stages of data condensation, data display, and conclusion drawing, while data validity was tested through source, technique, and time triangulation. The results showed that curriculum integration was implemented systematically through management functions that included planning, organizing, implementation, and evaluation. The implementation of the integrated curriculum was realized through a combination of academic learning, diniyah education, Qur’an tahfiz, character development, and extracurricular activities. This integration had a positive impact on graduate quality, as indicated by improved academic achievement, mastery of religious knowledge, social skills, leadership ability, and the strengthening of Islamic character. The conclusion of this study affirms that effective curriculum integration management makes an important contribution to shaping santri graduates who are excellent, competitive, and noble in character. These findings imply the need to strengthen integrated curriculum governance in pesantren as a model of Islamic education that is adaptive to national academic demands while remaining consistent in preserving Islamic values.